Integration of Experience and Achievements in the Development of Performing Skills of Kazakh Dance in Higher Education Institutions of the Republic of Kazakhstan - Kenzhetaeva, Aliya; Aitkalieva, Karlgash; Amreyeva, Tolkyn (Harmonia: Journal of Arts Research and Education, 2023)
The main purpose of this research is to study the experience and achievements of previous generations of folk dance performers to improve work with future choreographers who study Kazakh folk dance in higher education institutions of the Republic of Kazakhstan. The study’s methodological approach is the search and theoretical analysis of sources aimed at studying both the history of the Kazakh folk dance itself and the development of the performing skills methods of Kazakh dance in future choreographers. This research uses typological, historical, and thematic analysis methods from used literature collected during the writing of the article. The author analyzes the historical stages of the development of the professional training of choreographers-performers and the influence of the experiences and achievements of previous generations on the performing skills of future choreographers in Kazakh higher educational institutions. This study also found that modern teaching is based on the integration of experience and achievements in the art of choreography for the development of performing skills and choreographer-performer skills of Kazakh folk dances in higher educational institutions of the Republic of Kazakhstan. This research work is of practical importance in the study, as well as training of future choreographers who study dance in various areas of original folk art in higher education institutions of the Republic of Kazakhstan.